2009
DOI: 10.1186/ar2863
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor promotes articular damage by increased osteoclastogenesis in patients with rheumatoid arthritis

Abstract: IntroductionA protein analysis using a mass spectrometry indicated that there are serum proteins showing significant quantitative changes after the administration of infliximab. Among them, connective tissue growth factor (CTGF) seems to be related to the pathogenesis of rheumatoid arthritis (RA). Therefore, this study was conducted to investigate how CTGF is associated with the disease progression of RA.MethodsSerum samples were collected from RA patients in active or inactive disease stages, and before or af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 42 publications
(52 reference statements)
2
58
0
Order By: Relevance
“…Of the nine genes Articles in our group that met the more stringent false discovery rate, interestingly ZC3H12B encodes a protein with a role in proinflammatory actions of macrophages (31). In addition, connective tissue growth factor (CTGF) is associated with several functions including fibrosis, angiogenesis, and tumorigenesis and is believed to play a role in inflammatory disorders including rheumatoid arthritis and CTGF polymorphisms are associated with systemic sclerosis (32)(33)(34). Limitations of the study include small sample size, lack of patients with periodic fever or malignancy, sampling bias, and lack of a replication cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Of the nine genes Articles in our group that met the more stringent false discovery rate, interestingly ZC3H12B encodes a protein with a role in proinflammatory actions of macrophages (31). In addition, connective tissue growth factor (CTGF) is associated with several functions including fibrosis, angiogenesis, and tumorigenesis and is believed to play a role in inflammatory disorders including rheumatoid arthritis and CTGF polymorphisms are associated with systemic sclerosis (32)(33)(34). Limitations of the study include small sample size, lack of patients with periodic fever or malignancy, sampling bias, and lack of a replication cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Manns and coworkers also showed that CTGF is up-regulated in an experimental animal model of RA and that treatment with thrombospondin 1-derived peptide is associated with the down-regulation of CTGF occurring simultaneously with the amelioration of the disease (19). We have previously shown that CTGF enhances osteoclastogenesis in patients with RA and plays an important role in the pathogenesis of RA (6). Osteoclasts are commonly found within the erosive pit at the interface between the synovial inflammatory tissue and subchondral bone (20).…”
Section: Discussionmentioning
confidence: 89%
“…Several known hypoxia-regulated proteins have been shown to drive osteolytic bone metastases. Connective tissue growth factor (Higgins et al 2004 ) is involved in osteoclastogenesis and bone resorption, liberating tumorpromoting factors from the bone matrix (Kang et al 2003 ;Nozawa et al 2009 ). These tumor-promoting factors include bone morphogenic proteins and transforming growth factor-β, which also are upregulated by hypoxia signaling (Falanga et al 1991 ;Maegdefrau et al 2009 ).…”
Section: Hypoxia and The Selection Of Metastatic Sitesmentioning
confidence: 99%